Pengembangan Video Pembelajaran Interaktif Berbasis Model Quantum Teaching Dalam Meningkatkan Motivasi Dan Hasil Belajar Ipa Siswa Kelas V Sekolah DasarKhofifah - Khofifah (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The motivation and learning outcomes of fifth-grade elementary school students in science, especially on the topic of energy, are still low, necessitating interactive and contextual learning media. This study aims to develop interactive learning videos based on the Quantum Teaching model and examine their effectiveness in improving students’ motivation and learning outcomes. The research method used was Research and Development (R&D) with the ADDIE model, including analysis, design, development, implementation, and evaluation stages. The subjects were 29 students of class VA at UPTD SDN 2 Karangkendal. The learning video was developed using Canva for visual design and Capcut for audio-visual editing. Expert validation results indicated that the media is feasible for use and categorized as highly feasible. Classroom implementation showed increased student motivation, active participation during learning, and improved understanding of energy concepts. The average student score increased from 68.2 in the pretest to 86.7 in the posttest. In conclusion, interactive learning videos based on the Quantum Teaching model are effective in enhancing motivation and science learning outcomes for fifth-grade elementary students. Keywords: Interactive Learning Video, Quantum Teaching, Learning Motivation, Learning Outcomes, IPA Abstrak Motivasi dan hasil belajar IPA siswa kelas V sekolah dasar masih rendah, terutama pada materi energi, sehingga diperlukan media pembelajaran yang interaktif dan kontekstual. Penelitian ini bertujuan untuk mengembangkan video pembelajaran interaktif berbasis model Quantum Teaching dan mengetahui efektivitasnya dalam meningkatkan motivasi dan hasil belajar siswa. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model ADDIE, meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian adalah 29 siswa kelas VA UPTD SDN 2 Karangkendal. Video pembelajaran dikembangkan menggunakan Canva untuk desain visual dan Capcut untuk pengeditan audio-visual. Hasil validasi ahli menunjukkan media layak digunakan dengan kategori sangat layak. Implementasi media di kelas menunjukkan peningkatan motivasi belajar siswa, keterlibatan aktif selama pembelajaran, serta pemahaman konsep energi yang lebih baik. Nilai rata-rata siswa meningkat dari 68,2 pada pretest menjadi 86,7 pada posttest. Kesimpulannya, video pembelajaran interaktif berbasis Quantum Teaching efektif untuk meningkatkan motivasi dan hasil belajar IPA siswa kelas V sekolah dasar. Kata kunci: Video Pembelajaran Interaktif, Quantum Teaching, Motivasi Belajar, Hasil Belajar, IPA